Enhanced electrochemical performance of iron-manganese based cathode by Li doping for sodium-ion batteries. (1st December 2018) - Ding, Zhiyu; Liu, Yanchen; Tang, Qiming; Jiang, Qin; Lu, Juan; Xiao, Zhenzhao; Yao, Penghui; Monasterio, Manuel; Wu, Junwei; Liu, Xiangli
Abstract: In sodium ion battery, cathode material is the key factor affecting the cycle life, safety and energy density, so the development of high performance embedded sodium cathode material is always the top priorities in this aspect. Among cathode material candidates, the iron-manganese based transition metal oxides attracts lots of attentions due to the relevant high specific capacity (190 mAhg −1 ); however, their wide application is still hampered by the phase transition at high voltage. In this study, we successfully synthesize a P2-type Na0.6 Li0.2 Fe0.2 Mn0.6 O2 through the self-combustion reaction (SCR) method, which shows high stability during cycling. The capacity of the Na0.6 Li0.2 Fe0.2 Mn0.6 O2 is 167 mAhg −1 at the current density of 1/15 C, which shows 78% capacity retention over 100 cycles. At 1C current density, the material still maintains a specific capacity of 90 mAhg −1 at 250 cycles. It is suggested that the addition of Li improves the structural stability of the iron-manganese based transition metal oxides and the average working voltage. Graphical abstract: Highlights: A new cathode material Na0.6 Li0.2 Fe0.2 Mn0.6 O2 for sodium ion batteries was synthesized. High capacity retention (70%) over 250 cycles at 1C. Phase transition study through ex-situ XRD.